2007
DOI: 10.2337/dc07-0642
|View full text |Cite
|
Sign up to set email alerts
|

Increased Body Iron Stores of Obese Women With Polycystic Ovary Syndrome Are a Consequence of Insulin Resistance and Hyperinsulinism and Are Not a Result of Reduced Menstrual Losses

Abstract: OBJECTIVE -Increased serum ferritin levels, indicating increased body iron stores, have been found in overweight and obese women with polycystic ovary syndrome (PCOS). This finding might result from reduced menstrual losses secondary to oligo-or amenorrhea or from hyperinsulinism secondary to insulin resistance, because insulin favors the intestinal absorption and the tissue deposition of iron. To explore which of these mechanisms is responsible for the increase in body iron stores in women with PCOS, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 32 publications
2
57
0
1
Order By: Relevance
“…Polycystic ovary syndrome is not only a gynecological condition affecting reproductive age women, but also a syndrome comprehensive with a variety of metabolic disorders associated commonly with PCOS [21]. The present result was demonstrate that G1and G2 patients have significant elevation of BMI, and no significant difference in G3and G4 patients as compared with normal healthy group Table (1).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Polycystic ovary syndrome is not only a gynecological condition affecting reproductive age women, but also a syndrome comprehensive with a variety of metabolic disorders associated commonly with PCOS [21]. The present result was demonstrate that G1and G2 patients have significant elevation of BMI, and no significant difference in G3and G4 patients as compared with normal healthy group Table (1).…”
Section: Discussionsupporting
confidence: 63%
“…Transferrin saturation percent (%TS) was significantly elevated patients of G1, G2, G3, and G4 as compared with control. The fact that high intake of dietary iron and obesity may facilitate the intestinal absorption caused deposition of iron tissue [21,36]. Transferrin concentration and serum total iron binding capacity were significantly decreased in G1 patients of PCOS and increased in groups G2, G3 and G4 in compared with normal healthy groups, this explained due erythropoietin which has been effected by hyperandrogenemia, that is widely known as a critical component of PCOS.…”
Section: Discussionmentioning
confidence: 67%
“…However, although Diane 35 Diario is still considered a safe drug for the treatment of PCOS (34) and it has been suggested that the risk of thrombotic events in women taking oral contraceptives containing ethinyl-estradiol plus cyproterone acetate (the components of Diane 35 Diario) does not appear to be higher than that observed with other third generation oral contraceptive pills, this issue is still a matter of debate (35). Therefore, although the overall effect of oral contraceptives on the classic and nonclassic cardiovascular risk markers associated with PCOS is beneficial in our experience (3,(15)(16)(17)(18), it must be noted that others have reported an undesirable impact of contraceptive pills on the cardiovascular risk profile of these women (36)(37)(38). Diario, whereas white circles represent the data from the PCOS women on metformin.…”
Section: Discussionmentioning
confidence: 70%
“…Despite the beneficial impact of metformin on some aspects of the cardiovascular risk profile of PCOS women (15,16), metformin might reduce vitamin B 12 absorption thereby increasing homocysteine levels (39). Considering that homocysteine increases the rate of synthesis of tissue factor, which in turn activates the extrinsic coagulation pathway (27), the finding of an increase in plasma homocysteine concentrations during treatment with metformin suggests that this mechanism may contribute to the parallel changes in prothrombin time and activity observed in our patients.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation